PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE KEPALA BERNOMOR STRUKTUR TERHADAP KEMANDIRIAN DAN KERJA KERAS SISWA - ., muhyani; Dahlia, Dida (ATTA`DIB, 2015)
The aim of research is to know how independence value and hard work on math lesson at class II before and after applying a model of cooperative learning type Numbered Head Structure. This research is qualitative which conducted a quasi experimental design. Based on data, the research found that both independence value and hard work on math lesson before applying the model is relatively small, about 56.4453. But after applying the model, both independence value and hard work on math lesson increases significantly about 70.6667. However this model gives an influence to the students. The significance of this research is model of cooperative learning type Numbered Head Structure has a positive effect to the independence value and hard work of students class II on math lesson.